Catatan tentang Perencanaan Tembok Laut untuk Mitigasi Bencana Tsunami - Triatmadja, Radianta; Warniyati, Warniyati (Department of Civil Engineering, Diponegoro University, 2021)
Many coastal structures or structures in coastal areas were destroyed by a tsunami attack. Such destructions were due primarily to the fact that such structures were not designed to withstand a tsunami. Those which were designed to withstand tsunami force may also have been destroyed due to some damaging factors which were not included in the design. The damage of the coastal structures is one of the important factors that have caused casualties. Especially, when the destroyed structures were originally aimed to mitigate the area against tsunami, they may cause higher fatalities. Examples of such structures are sea walls in many parts of Japan which were destroyed by the 2011 tsunami. This paper discusses the important factors relevant to the damage of seawall as tsunami mitigation structure such as impact force due to tsunami front, hydrostatic force, and hydrodynamic force, debris force and scour due tsunami. The study was carried out based on literature about the damages of seawall as tsunami protection structures and laboratory experiment reports. The destructions to the structures were divided into three classifications namely instantaneous direct destruction due to impact and drag forces, slowly direct destruction due to drag force, and slowly indirect destruction due to scour. Finally, important aspects to be considered in the design of seawall as tsunamis protection were proposed.